Peritoneal Malignancy in Children: A Pictorial Review. Issue 4 (November 2016) - James, Karl M.; Bogue, Conor O.; Murphy, Amanda J.; Navarro, Oscar M.
Peritoneal malignancies are a rare occurrence in children, often metastatic and rarely originating primarily in the peritoneum. The imaging findings of these entities in the pediatric age have not been recently reviewed or they have been previously described or depicted mostly as part of articles discussing each entity separately. This is a review of the most relevant peritoneal malignancies in childhood emphasizing imaging features. Knowledge of these appearances may facilitate diagnosis and staging of these neoplasms.